2007
DOI: 10.1161/circulationaha.107.706226
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Position, Race/Ethnicity, and Inflammation in the Multi-Ethnic Study of Atherosclerosis

Abstract: Background-Low socioeconomic position is known to be associated with cardiovascular events and atherosclerosis.Reasons for these associations remain a topic of research. Inflammation could be an important mediating mechanism linking socioeconomic position to cardiovascular risk. Methods and Results-This cross-sectional study used data from the baseline examination of the Multi-Ethnic Study of Atherosclerosis (MESA), a study of 6814 men and women 45 to 84 years of age. Race-and ethnicity-stratified regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
105
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(114 citation statements)
references
References 33 publications
9
105
0
Order By: Relevance
“…We confirmed this finding within the SWAN cohort, where we found educational level to be the most informative SES predictor of CRP concentrations. The impact of ethnicity and SES on CRP concentrations was also examined in the MESA cohort (35 ), where educational level was found to be a strong predictor of CRP. Yet in MESA, further examination in multivariate models found that the relationship between CRP and SES persisted only in whites, with substantial confounding by metabolic factors, adiposity, and behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed this finding within the SWAN cohort, where we found educational level to be the most informative SES predictor of CRP concentrations. The impact of ethnicity and SES on CRP concentrations was also examined in the MESA cohort (35 ), where educational level was found to be a strong predictor of CRP. Yet in MESA, further examination in multivariate models found that the relationship between CRP and SES persisted only in whites, with substantial confounding by metabolic factors, adiposity, and behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Critical care research 16,17 (nonspecific to trauma) has shown that African Americans and persons of low socioeconomic status have nearly twice the rates of sepsis, organ dysfunction, and sepsis-related mortality as do whites. Low socioeconomic status has been associated with high levels of baseline inflammation, 18 a finding related to early organ dysfunction. 19,20 Few data on these outcomes specific to trauma are available.…”
mentioning
confidence: 99%
“…Much of this socioeconomic status relationship can be attributed to CVD and the combined effects of disparities in health-related behaviours, environmental conditions, social structures, and the contact and delivery of health care. Because these factors change in developed and developing countries and because they are modifiable, it is important to compare countries to find ways to reach people with different ways of life [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%